Agricultural productivity in the northern area of the province of Esmeraldas, Ecuador (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
In the context of Ecuador's economic and social development, theagricultural sector plays a fundamental role, and currently presentsdifferent challenges in terms of increasing productivity, so thepurpose of this research is to analyze the factors that influenceagricultural productivity in the northern area of the Province ofEsmeraldas. It was conducted under the quantitative approach, witha descriptive type of research, the target population of the study werethe producers of Eloy Alfaro Canton, located in Borbón, La Tola andother parishes, for which a sample of one hundred producers wasconsidered. The data collection technique was the survey, whoseinstrument consists of a questionnaire with a Likert-type scale, thedata were analyzed using descriptive statistics, with the calculation ofthe relative percentage frequency. As a result of the measurementsmade in terms of the economic dimension, it was found that mostproducers do not invest in crop maintenance and livestock activities,which results in risky production conditions; while, in the knowledgedimension, producers do not invest in maintenance or in innovationand technology, do not know processes and techniques to developagricultural activities, do not have the organization and control of the processes they carry out, and therefore require training and technicalassistance to increase productivity and be competitive in the market.